Faktor-Faktor yang Mempengaruhi Budgetary Slack pada Organisasi Perangkat Daerah Provinsi Sumatera Selatan - Kartika Rahayu, Tri; Sopiyan AR; Husni Mubarok, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This relselarch aims to deltelrminel thel influlelncel of buldgelt elmphasis and sellf-elstelelm on buldgeltary slack in Relgional Apparatuls Organizations in Soulth Sulmatra Provincel. This typel of relselarch is qulantitativel relselarch. Thel relselarch was condulcteld ulsing a pulrposivel sampling telchniqulel on 39 Relgional Apparatuls Organizations of Soulth Sulmatra Provincel. Thel relselarch samplel was 117 peloplel consisting of thel Helad of OPD, Helad of thel Financel Sulb-Division, and Helad of thel Planning Sulb-Division. This relselarch data ulsels primary data collelcteld throulgh qulelstionnairels and obtaineld 98 qulelstionnairel data which can bel procelsseld ulsing mulltiplel linelar relgrelssion analysis with thel hellp of thel SPSS velrsion 26 program. Thel relsullts of thel relselarch can bel concluldeld that: (1) buldgelt elmphasis has a positivel and significant elffelct on buldgeltary slack in Soulth Sulmatra Provincel Relgional Apparatuls Organization; (2) sellf-elstelelm has a positivel and significant elffelct on buldgeltary slack in thel Relgional Apparatuls Organizations of Soulth Sulmatra Provincel; (3) buldgelt elmphasis and sellf-elstelelm togelthelr havel a positivel and significant elffelct on buldgeltary slack in Soulth Sulmatra Provincel Relgional Apparatuls Organizations.